Uma coalizão de design para a transformação social : propondo diálogos estratégicos entre ecossistemas criativos - Bueno, Aline Callegaro de Paula (Universidade do Vale do Rio dos Sinos, 2018)
In a scenario where economic inequality, damage to the environment and social exclusion are accentuated, groups of people have been working to change the reality around them in search of more sustainable ways of living. Such groups carry out activities that promote social innovations and represent possible alternatives to the dominant logic of production, consumption and conviviality. In the scope of strategic design, these groups of people are understood as creative ecosystems, in which several actors interact and produce innovative actions with transforming potential. In Porto Alegre, we identified creative ecosystems that carry out processes and practices of social innovation in terms of managing their initiatives, production, resistance and social interaction. These are: collaborative houses, collective production spaces, urban occupations and shared housing. Although there are specific characteristics of each, they have convergent values and purposes that point to a more just, egalitarian, democratic and resilient society. In this sense, they are initiatives that collaborate to achieve the Sustainable Development Goals listed by the United Nations in 2015. The intention of this research is to explore, from a strategic design perspective, the integration of such creative ecosystems so that, with this connection, strengthen themselves and be able to configure themselves as a viable alternative to the dominant logic of the ways of being and doing, especially in the city of Porto Alegre. To do this, we mapped and analyzed its activities so that it was possible to propose, from concepts derived from Manzini and Morin, a design coalition through strategic dialogues and collaborative encounters. This research therefore seeks to contribute to the discussions about design for social innovation and sustainability in a Brazilian context.
Keywords: Design estratégico; Inovação social; Desenvolvimento sustentável; Coalizão de design; Diálogo estratégico; Strategic design; Social innovation; Sustainable development; Design coalition; Strategic dialog; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial